ISLAMIC BANK’S PROFIT GROWTH IN INDONESIA: BANK HEALTH RATING FACTOR APPROACH - Tilawah, Yovindra Balqis; Amalia, Alvien Nur (Jurnal Syarikah : Jurnal Ekonomi Islam, 2021)
This study aims to determine the effect of the factors forming the level of soundness of the bank Risk Profile, Good Corporate Governance, Earning and Capital on profit growth. The object of research is Islamic Commercial Bank operating in Indonesia from 2014 to 2018. The technique used in sampling is purposive sampling so that 50 observations are obtained. The analytical tool used is Eviews9. The results of the study stated that the assessment of the level of soundness of the bank Risk Profile, Good Corporate Governance, Earning and Capital simultaneously influence profit growth. Partially, the Risk Profile measured by the NPF ratio has a negative effect, while Good Corporate Governance, which is measured by the BOPO ratio, and the Capital measured by the CAR ratio has a positive effect on profit growth. Earning variable measured by ROA ratio has no effect on earnings growth.